2019
DOI: 10.1093/eurheartj/ehz115
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide-Y causes coronary microvascular constriction and is associated with reduced ejection fraction following ST-elevation myocardial infarction

Abstract: Aims The co-transmitter neuropeptide-Y (NPY) is released during high sympathetic drive, including ST-elevation myocardial infarction (STEMI), and can be a potent vasoconstrictor. We hypothesized that myocardial NPY levels correlate with reperfusion and subsequent recovery following primary percutaneous coronary intervention (PPCI), and sought to determine if and how NPY constricts the coronary microvasculature. Methods and results Peripheral venous NPY levels were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 29 publications
5
42
2
3
Order By: Relevance
“…cTnI is routinely assessed in patient samples in clinical laboratories to detect myocardial damage, with a clinical range for at‐risk patients of >0.03 ng/ml 27 . NPY is a sympathetic cotransmitter and critical to cardiovascular homeostasis including cardiac remodeling and angiogenesis 28,29 . It has been correlated to stress, anxiety, and posttraumatic stress disorder 30,31 at a clinically relevant level of ≤1.5 ng/ml 32 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…cTnI is routinely assessed in patient samples in clinical laboratories to detect myocardial damage, with a clinical range for at‐risk patients of >0.03 ng/ml 27 . NPY is a sympathetic cotransmitter and critical to cardiovascular homeostasis including cardiac remodeling and angiogenesis 28,29 . It has been correlated to stress, anxiety, and posttraumatic stress disorder 30,31 at a clinically relevant level of ≤1.5 ng/ml 32 .…”
Section: Introductionmentioning
confidence: 99%
“…27 NPY is a sympathetic cotransmitter and critical to cardiovascular homeostasis including cardiac remodeling and angiogenesis. 28,29 It has been correlated to stress, anxiety, and posttraumatic stress disorder 30,31 at a clinically relevant level of ≤1.5 ng/ml. 32 Our results showed that PRADA achieved highly sensitive detection of both biomarkers of acute myocardial infarction ideal for risk stratification.…”
mentioning
confidence: 99%
“…NPY causes coronary microvascular constriction and reduced EF following ST-elevation MI via NPY1R that is a predominant receptor subtype in the heart (Chottova Dvorakova et al, 2008; Herring et al, 2019). So, to see whether NPY1R was involved in NPY/miR-499 and NPY/FoxO4 axis, we determined the mRNA level of miR-499 by NPY1R antagonist in MI in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…NPY significantly increases infarct area in relation to the area at risk during myocardial ischemia–reperfusion (I/R) injury, which is blunted by NPY1R antagonist BIBO3304 (Herring et al, 2019). So, we want to see whether NPY1R antagonist BIBO3304 inhibits H 2 O 2 -induced cardiomyocyte apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…The role of cardiac afferent neurotransmission in parasympathetic function is still under investigation . Inhibition of acetylcholine release may also occur at the nerve‐myocyte interface by the high levels of norepinephrine, as well as sympathetic neuropeptides, such as neuropeptide Y, though this area remains in need of further investigation.…”
Section: Pathophysiology Of Ventricular Arrhythmias In Heart Diseasementioning
confidence: 99%